The Influence of Customer Experience and Brand Trust on Repurchase Intentions by Moderating Sales Promotions at PT Wika Beton Region II - Aldila, Tino Yose; Helmi, Sulaiman; Fitriasuri; Mellita, Dina (Sinergi International Journal of Management and Business, 2025)
Priority in government development programs is an opportunity for construction companies to increase sales. However, in practice, PT Wika Beton Wilayah II Palembang City, as a leading construction company, has failed to get new projects. This study aims to determine and analyze the effect of customer experience and brand trust on repurchase intention with moderation of sales promotion. The research was conducted using quantitative methods through SEM-PLS analysis, sourced from questionnaires distributed to 49 respondents. Respondents are customers of PT Wika Beton Region II Palembang City who have made purchases more than once. The results of the study are expected to reveal that customer experience and brand trust can influence customer repurchase intention moderated by sales promotion. The predicted influence is a significant favorable influence, both partially and simultaneously. The results of this study are expected to be used as a reference for the formulation of marketing strategy formulation strategies for policymakers in the company.